1998
DOI: 10.3758/bf03211920
|View full text |Cite
|
Sign up to set email alerts
|

Inertial eigenvalues, rod density, and rod diameter in length perception by dynamic touch

Abstract: Four experiments addressed the relevance of the eigenvalues I k of the inertia tensor for perceiving length by dynamic touch. Experiments 1-2 focused on the consequences of limiting variation in the minimum eigenvalue 1 3 , Both revealed that perceived length is a function of I k . Whether the contribution of 1 3 is detected, however, depends on the range of values that characterize a particular object set. Experiments 3-4 considered the relationship between an independent index of a rod's diameter, which does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
3
28
1
Order By: Relevance
“…To be more exact, the type of scaling observed in the present results appears to be a definite scaling rather than an absolute scaling (Bingham, 1993(Bingham, , p. 1155. That is, although the participants did not exactly reproduce the absolute lengths of the rods in both media, they were able to provide estimates that were consistently within a marginal tolerance of actual values and were not merely reproducing a relative ordering of rod lengths (see Carello, Fitzpatrick, Flascher, & Turvey, 1998). The perceptions were a function of information more definite than that which would only support relative scaling.…”
Section: Resultsmentioning
confidence: 88%
“…To be more exact, the type of scaling observed in the present results appears to be a definite scaling rather than an absolute scaling (Bingham, 1993(Bingham, , p. 1155. That is, although the participants did not exactly reproduce the absolute lengths of the rods in both media, they were able to provide estimates that were consistently within a marginal tolerance of actual values and were not merely reproducing a relative ordering of rod lengths (see Carello, Fitzpatrick, Flascher, & Turvey, 1998). The perceptions were a function of information more definite than that which would only support relative scaling.…”
Section: Resultsmentioning
confidence: 88%
“…For instance, high correlations have been reported between I 1 (either alone or in combination with I 3 ) and the perceived length of an object (Carello, Fitzpatrick, Flascher, & Turvey, 1998;Fitzpatrick et al, 1994;Pagano et al, 1993;Solomon & Turvey, 1988;Solomon, Turvey, & Burton, 1989;Turvey, Burton, Amazeen, Butwill, & Carello, 1998). In addition, perceived object width has been found to correlate with the eigenvalues of the inertia tensor .…”
mentioning
confidence: 99%
“…Specifically, I 1 and I 3 have been claimed to form the basis of length perception (Carello, Fitzpatrick, Flascher, & Turvey, 1998;Fitzpatrick et al, 1994;Stroop, Turvey, Fitzpatrick, & Carello, 2000;Turvey, Burton, Amazeen, Butwill, & Carello, 1998), a task that has been studied extensively in dynamic touch. However, Kingma, Beek, and van Dieën (2002) have demonstrated that the identification of I 1 and I 3 as the informational basis of length perception suffered from confounding covariation between candidate mechanical invariants.…”
mentioning
confidence: 99%